Analisis Pengukuran Produktivitas Bagian Produksi Dengan Metode Objective Matrix (Omax) Pada Pabrik Roti Dinamis - Sembiring, Dessy Siar Rehulina Br; Wahyudi, Rizqi; Nugraha, Andhyka Tyaz (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2025)
Dynamic Bread Factory has suffered a very significant failure to reach the production target by finding a large number of defective products so that the use of materials becomes inefficient and also often the breakdown of the processing machine which affects the quantity of the final product becomes unoptimal. The study aims to analyze the index of productivity value on the production part of the Dynamic Bread Factory, identify factors causing the fluctuation of the production index and provide suggestions for improvements that can affect the increase in productiveness. OMAX methods and fishbone diagrams to measure and analyze productivity indices. The data processing results showed that the index varied, with the highest index in November increasing by 215.48% while the lowest in October experienced a significant decline of 73.50%. Five productivity ratios that have been measured indicate that ratio 1 and ratio 2 have the lower yields that are the cause of low productivities in the Dynamic Bread Factory.